Respuesta :
We would first rearrange
2/3*x-1/2-(x+7/6)=0
Reduce 7/6
(-2(x+5)/6= 0*6
Solve : -2 = 0
Subtract 5 from both sides
x = -5
Your answer: x = (-5)
2/3*x-1/2-(x+7/6)=0
Reduce 7/6
(-2(x+5)/6= 0*6
Solve : -2 = 0
Subtract 5 from both sides
x = -5
Your answer: x = (-5)
2/3x - ½= x + 7/6
+ 1/2 + 1/2
2/3x = x + (7/6 + 1/2)
2/3x = x + 5/3
2x/3
2x/3 = x + 5/3
*3 *3
2x = 3x + 5
-3x -3x
-x = 5
x = -5
Your answer is -5
Hope I helped!
Let me know if you need anything else!
~ Zoe
+ 1/2 + 1/2
2/3x = x + (7/6 + 1/2)
2/3x = x + 5/3
2x/3
2x/3 = x + 5/3
*3 *3
2x = 3x + 5
-3x -3x
-x = 5
x = -5
Your answer is -5
Hope I helped!
Let me know if you need anything else!
~ Zoe